The Mythical Norm in Costume Design - Parker, Megan (Curtin University, 2024)
This research explores and evaluates current practices in costume design and realisation for stage musicals. It aims to understand their contribution to the acceptance of uniformity of physical characteristics in performers, and whether this leads to the idealisation of specific body types. The exegesis considers ways bodies from historically marginalised identities are perceived in society, popular culture and on stage with reference to feminist texts and literature from fat and disability studies.